Exploring fibrous ingredients for fish: The case of feeding sugar beet pulp to tambaquí (Colossoma macropomum) - Awot Teklu Mebratu; Leilani Vanhandsaeme; Yohannes Tekle Asfaw; Wouter Merckx; Geert Paul Jules Janssens (Heliyon, 2023)
For a long time, co-products of food processing have been used in animal feed, but far less in fish because of their assumed inability to cope with high-fiber diets. Research on feeding co-products to fish species that naturally consume fibrous diets are yet lacking. We here evaluated the impact of sugar beet pulp in the diet of tambaquí on nutrient metabolism, oxidative stress, inflammation, and intestinal histomorphometry. A total of 18 tambaquí fish (1616 ± 107 g; 2 years old) were randomly divided over 6 similar tanks with 3 fish per tank and randomly attributed to one of the six dietary treatments 0, 5, 10, 15, 20 and 25 % beet pulp addition and reared for 8 weeks. Water quality parameters (pH, NH3–N, EC, TDS, DO, and temperature) were assessed and recorded twice a week for each tank. A quadratic increase in intestinal villus length, paravilli and absorptive surface were observed with beet pulp addition. Ammonia and pH as quality indicators were significantly changing with beet pulp addition. A higher supply of glucogenic substrate to the citric acid cycle was noticed with beet pulp addition due to the positive correlation with blood propionylcarnitine: acetylcarnitine ratio while there was no effect on ketone body synthesis as measured through the 3-hydroxybutyrylcarnitine: acetylcarnitine ratio. No pronounced change of serum and whole fish histamine and lowered concentrations of serum malondialdehyde were observed with beet pulp addition. In conclusion, beet pulp induced a marked increase in intestinal villus architecture without signs of inflammation or oxidative stress. Large-scale studies need to clarify if these features lead to improved growth performance but this work opens options for further study. The non-linear pattern of some blood components with increasing beet pulp may call for future optimal dosing and feed form of beet pulp together.